African Continental Free Trade Area Agreement - Does the Facts Support the Benefits for Nigeria? (2020)
Hesitantly, but finally, Nigeria joined the African Continental Free Trade Area (AfCFTA) with the Nigerian President, Mohammadu Buhari, signing the protocol at the African Union Summit in Niamey on July 7, 2019 based on perceived benefits. This study interrogated the purported benefits for Nigeria using standard trade costs between Nigeria and peer countries in Africa. Using a content analytical framework on a dataset by World Development Indicators and World Integrated Trade Solutions, the study found that average tariff rate in Nigeria is very high when compared to that of her major trading rivals in Africa like Ghana, Egypt and South Africa. Furthermore, the study found Nigeria in a comparative disadvantaged position on the ease of doing business in the same setting. Also, Nigeria’s major export commodity is crude oil and lubricants which has little or no market in the continent. Besides, trade-related infrastructure, especially roads and maritime corridors, in Nigeria is poor even by African standards. With these structural problems, ipso facto, Nigeria may not benefit maximally and comparatively in the enlarged continental market envisioned by the AfCFTA agreement. The study therefore, recommended that Nigerian government should continue to maintain the present cautious approach and refrain from making further commitments on the AfCFTA deal. In the meantime, the country should embark on massive infrastructural and trade-related development, improve the ease of doing business and diversify the economy in order to be in vintage position to exploit the potential opportunities offered by the AfCFTA in the medium-to-long term horizon.